Experimental research on parameter selection of echo hiding in voice - Li Li; Ya-Qi Song (2009 International Conference on Machine Learning and Cybernetics, 2009)
Echo hiding can effectively place imperceptible information into an audio data stream. Many improvements are developed for echo hiding system, but there is not an intensive study on the parameter selection of echo hiding. Based on the speech signals with various sampling rate and single echo hiding scheme, this work explores the regular pattern of recovery accuracy and key parameters, and presents a series of parameter selection solution with a good hiding effects. Experimental results reveal that the proposed values range of key parameters can yield well performance in recovery accuracy. The results are useful for practical applications.